Stigma, Support Initiatives and the “Directors’ Dilemma“: is anyone mitigating the socio-economic impact of HIV and AIDS related stigma in Botswana? - Geiselhart, Klaus (2006)
The article explains the socio-economic impact of HIV/AIDS-related stigma in Botswana. It identifies self-help initiatives as those who mitigate the impact and explains the most severe problems they face. This paper is a revised version of the presentation given at the workshop "Changing HIV and AIDS impact patterns in the wake of the ARV therapy" in Gaborone/ Botswana.